iNOS Promotes the Development of Osteosarcoma via Wnt/β-Catenin Pathway - Wei Chu; Lirong Cao; Gui Daokun; Jiali Zhao (Journal of Immunology Research)
Inducible nitric oxide synthase (iNOS), accompanied with protumor and antitumor activity, has been studied in multiple cancers. However, the role of iNOS expression in osteosarcoma (OS) is far from being fully understood. In present work, iNOS levels were detected in OS tissues and cell lines. Colony formation assay, Transwell assay, and fow cytometer were used to assess proliferation, migration, invasion, and apoptosis abilities in vitro after iNOS inhibition. Western blotting determined the expressions of iNOS, MMP2, MMP9, C-MYC, Ki67, PCNA, and β-catenin. Mice transfected with OS cells were to evaluate tumor formation. IHC assay was to evaluate the expressions of iNOS and β-catenin in mice. The results showed that iNOS was upregulated in both OS tissues and cells compared with that in matched normal tissues or cells. And we found that proliferation, migration, and invasion numbers of OS cells were decreased, and apoptosis numbers of OS cells were increased after iNOS inhibition. MMP2, MMP9, C-MYC, Ki67, and PCNA levels were also reduced in OS cells treated with iNOS inhibition. Else, iNOS inhibition would suppress β-catenin expression in OS cells to regulate MMP2, MMP9, C-MYC, Ki67, and PCNA expressions. In addition, tumor formation, iNOS expression, and β-catenin expression were inhibited in mice transplanted with iNOS knockout OS cells. These results indicated that iNOS might be a potential therapeutic target for OS.